2018
DOI: 10.1007/s42114-018-0042-5
|View full text |Cite
|
Sign up to set email alerts
|

Separation-free Al-Mg/graphene oxide composites for enhancement of urban stormwater runoff quality

Abstract: Separation-free Al-Mg/graphene oxide (Al-Mg/GO) composites were synthesized by facile one-pot hydrothermal treatment and examined for adsorptive removal of representative contaminants (phosphate, copper (II), and Diclofenac (DCF)) in urban stormwater runoff. The Al-Mg/GO composites exhibited good adsorption capacity for all three contaminants. The adsorption isotherm and kinetics are well described by Freundlich model and pseudo-second-order model, respectively. Further, adsorption of phosphate and DCF favored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…This shows that the contaminants on the highway surface neutralized the pH of direct rain. The low pH rainwater has SO 4 , which corrodes heavy metals and, as a result, neutralizes the stormwater (Ahmadi et al 2018). The pH of highway runoffs at each site remained within the environmental quality standards (Fig.…”
Section: Contaminant Event Mean Concentrationsmentioning
confidence: 94%
See 1 more Smart Citation
“…This shows that the contaminants on the highway surface neutralized the pH of direct rain. The low pH rainwater has SO 4 , which corrodes heavy metals and, as a result, neutralizes the stormwater (Ahmadi et al 2018). The pH of highway runoffs at each site remained within the environmental quality standards (Fig.…”
Section: Contaminant Event Mean Concentrationsmentioning
confidence: 94%
“…These high suspended solid concentrations increase the mortality rate of flora and fauna in the receiving stream by physically covering the benthic zone habitat (Chapman et al 2017). Various studies have reported the toxicity due to metals-laden suspended solid discharged into the streams (Ahmadi et al 2018). Chloride, chemical oxygen demand, and tot-N remained within the environmental quality standards at all the highway segments.…”
Section: Contaminant Event Mean Concentrationsmentioning
confidence: 99%
“…3 The predicted high demand of magnesium is also from its high demand in other fields, for example, paper manufacturing, fertilizer production, 4−6 and water/wastewater treatment. 7,8 Natural magnesium sources are magnesium-bearing ores, for example, dolomite, magnesite, brucite, and magnesium-containing waters, for example, salt lake brines, seawater, and geothermal water. 1,9 Besides, municipal and industrial wastewater can also be a significant source of magnesium but is often neglected.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Magnesium (Mg) is used in alloys with aluminum (Al) to make the cars lighter and also in new types of batteries; thus, its demand and price are predicted to grow rapidly over the next decades . The predicted high demand of magnesium is also from its high demand in other fields, for example, paper manufacturing, fertilizer production, and water/wastewater treatment. , Natural magnesium sources are magnesium-bearing ores, for example, dolomite, magnesite, brucite, and magnesium-containing waters, for example, salt lake brines, seawater, and geothermal water. , …”
Section: Introductionmentioning
confidence: 99%
“…Because the legislative standards for discharging nutrients into the environment are becoming increasingly stricter, a significant amount of scientific effort is going toward their removal. For example, N and P removal from different water matrices has been studied using biological nitrification and denitrification, metal ion precipitation, adsorption, , ammonia stripping, electrochemical conversion, ion exchange and microbial electrolysis. , One of the clean and effective methods of nitrogen removal from wastewater is electrochemical redox. The nitrate and ammonium ions can be converted to nontoxic nitrogen gas on active materials, such as Cu, Sn, and Ni metals or oxides .…”
Section: Introductionmentioning
confidence: 99%